Causes and Predictors of Readmission in Patients With Atrial Fibrillation Undergoing Catheter Ablation: A National Population‐Based Cohort Study. Issue 12 (19th June 2018) - Arora, Shilpkumar; Lahewala, Sopan; Tripathi, Byomesh; Mehta, Varshil; Kumar, Varun; Chandramohan, Divya; Lemor, Alejandro; Dave, Mihir; Patel, Nileshkumar; Patel, Nilay V.; Palamaner Subash Shantha, Ghanshyam; Viles‐Gonzalez, Juan; et al.
Abstract : Background: Reducing readmission after catheter ablation (CA) in atrial fibrillation (AF) is important. Methods and Results: We utilized National Readmission Data (NRD) 2010–2014. AF was identified by International Classification of Diseases, Ninth Edition, Clinical Modification (ICD‐9‐CM) diagnostic code 427.31 in the primary field, while first CA of AF was identified via ICD‐9 ‐procedure code 37.34. Any admission within 30 or 90 days of index admission was considered a readmission. Cox proportional hazard regression was used to adjust for confounders. The primary outcomes were 30‐ and 90‐day readmissions and the secondary outcome was AF recurrence. In total, 1 128 372 patients with AF were identified from January 1, 2010 to September 30, 2014. Of which 37 360 (3.3%) underwent CA. Patients aged ≥65 years and female sex were less likely to receive CA for AF. Overall, 10.9% and 16.5% of CA patients were readmitted within 30 and 90 days post‐CA, respectively. Most common causes of readmissions were arrhythmia (AF, atrial flutter), heart failure, pulmonary causes (pneumonia, chronic obstructive pulmonary disease) and bleeding complications (gastrointestinal bleed, intracranial hemorrhage). Patients with diabetes mellitus, heart failure, coronary artery disease (CAD), chronic pulmonary and kidney disease, prior stroke/transient ischemic attack (TIA), female sex, length of stay ≥2 and disposition to the facility were prone to higher 30‐ and 90‐day readmissions post‐CA. Predictors of increase in AF recurrence post‐CA were female sex, diabetes mellitus,  chronic pulmonary disease, and length of stay ≥2. Trends of 90‐day readmission and AF recurrence were found to improve over the study period. Conclusions: We identified several demographic and clinical factors associated with the use of CA in AF, and short‐term outcomes of the same, which could potentially help in the patient selection and improve outcomes.